1997
DOI: 10.1002/art.1780400614
|View full text |Cite
|
Sign up to set email alerts
|

The synovial expression and serum levels of interleukin‐6, interleukin‐11, leukemia inhibitory factor, and oncostatin m in rheumatoid arthritis

Abstract: Objective. To determine the expression of interleukin‐6 (IL‐6), IL‐11, leukemia inhibitory factor (LIF), and oncostatin M (OSM) and their major cellular sources in the joints of rheumatoid arthritis (RA) patients, as well as the correlation of circulating levels of these IL‐6‐type cytokines and C‐reactive protein (CRP). Methods. Messenger RNA (mRNA) and protein levels for IL‐6, IL‐11, LIF, and OSM were determined by using reverse transcription‐polymerase chain reaction and enzyme‐linked immunosorbent assay, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
146
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(161 citation statements)
references
References 45 publications
11
146
0
3
Order By: Relevance
“…It is secreted by activated T cells, monocytes, and neutrophils (13,14,41), and elevated levels of OSM are detected in the synovial fluid of patients with RA but not OA (9,10). Earlier studies clearly showed that OSM production in RA tissue correlated with the amount of leukocyte infiltration (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is secreted by activated T cells, monocytes, and neutrophils (13,14,41), and elevated levels of OSM are detected in the synovial fluid of patients with RA but not OA (9,10). Earlier studies clearly showed that OSM production in RA tissue correlated with the amount of leukocyte infiltration (9).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these therapeutic strategies are not beneficial to all patients, suggesting that other players must be involved in the pathogenesis. Various studies have shown that other cytokines such as IL-6, oncostatin M (OSM), IL-4, IL-13, and interferon-␥ (IFN␥) are also present in the synovial fluid of chronically inflamed joints (9)(10)(11).…”
mentioning
confidence: 99%
“…They strongly express a variety of activation markers, including surface molecules (e.g., major histocompatibility complex class II, CD13, or vascular cell adhesion molecule 1), and can thereby efficiently present antigens to T cells. In addition, fibroblast cell lines isolated from RA patients have the potential to produce matrix-degrading enzymes and several cytokines, such as IL-1, IL-6, IL-8, granulocyte-macrophage colony-stimulating factor (GM-CSF), and transforming growth factor ␤ (TGF␤) (31)(32)(33). In this study, we demonstrated that FLS were able to secrete large amounts of IL-15 and TNF␣, which were strongly induced by treatment with IL-1␤, IFN␥, and LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report that LIF is a pro-inflammatory mediator in a variety of inflammatory disorders (Table 1), while others point to an anti-inflammatory role ( Table 2). LIF is highly elevated in the synovial tissue and fluids of patients with rheumatoid arthritis [68][69][70]. In addition, human articular chondrocytes and synoviocytes produce LIF, which is strongly upregulated by other proinflammatory cytokines, such as IL-1, IL-6, IL-17, or TNF [71,72] and downregulated by the antiinflammatory cytokine IL-4 [73].…”
Section: Lif In Acute and Chronic Inflammationmentioning
confidence: 99%